2013
DOI: 10.1089/cell.2012.0089
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activation Requirements of Zona-Free Sheep Oocytes before and after Somatic Cell Nuclear Transfer

Abstract: In this study, the effect of the steps involved in zona-free somatic cell nuclear transfer (SCNT) on oocyte transcripts was investigated in sheep. To establish the reliable combined electrical-chemical activation for zona-free oocytes, oocytes were first exposed to an electrical pulse and then treated with 18 chemical activation regimens designed through modifying duration and concentration of ionomycin and 6-dimethyl aminopurine (6-DMAP), which is routinely used for SCNT. Electrofusion-mediated nuclear transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The cleavage percentage obtained in HMC was 66.92 ± 3.76% which was significantly higher than that obtained in conventional SCNT ( p < .05). Similar cleavage percentage has been observed with HMC in cattle and pig (Hajian et al., ; Lagutina et al., ). However, higher cleavage rates with similar technique have been obtained in goat (Khan et al., ) and buffalo (Shah et al., ).…”
Section: Discussionsupporting
confidence: 81%
“…The cleavage percentage obtained in HMC was 66.92 ± 3.76% which was significantly higher than that obtained in conventional SCNT ( p < .05). Similar cleavage percentage has been observed with HMC in cattle and pig (Hajian et al., ; Lagutina et al., ). However, higher cleavage rates with similar technique have been obtained in goat (Khan et al., ) and buffalo (Shah et al., ).…”
Section: Discussionsupporting
confidence: 81%
“…In cases of reproductive cloning in other mammalian species (Bordignon et al, 2013, Hajian et al, 2013, Kamimura et al, 2013), although the techniques have been perfected, manipulated embryos undergo developmental failure and the resulting offspring are found to succumb to early death, which is presumed to be coupled to unanticipated epigenetic events. Regarding somatic cell nuclear transfer (SCNT), a genome-wide study revealed that although an oocyte has the ability to epigenetically reprogram transplanted DNA, it cannot fully replicate the DNA demethylation which occurs during natural fertilisation.…”
Section: Mitochondrial Transfer Techniquesmentioning
confidence: 99%